Economic growth in Africa - Savvides, Andreas (My University, 1995)
This paper draws on the recent endogenous-growth methodology to study the factors behind differences in per capita growth rates across Africa. The results indicate that various economic factors including initial conditions, investment, population growth, trade orientation, inflation, financial development, and the growth of the government sector contribute significantly to economic growth. In addition to economic variables, we find the degree of political freedom to be a significant contributor to economic growth. Finally, we find some evidence that economic growth by the members of the CFA Franc Zone has not fared well in comparison to other African countries
Keywords: CFA franc zone; growth factor; Franc zone; endogenous growth theory; economic development; comparative study